Er-Doped BiVO4/BiFeO3 Nanocomposites Synthesized via Sonochemical Process and Their Piezo-Photocatalytic Application - Thanaphon Kansaard; Maneerat Songpanit; Russameeruk Noonuruk; Chakkaphan Wattanawikkam; Wanichaya Mekprasart; Kanokthip Boonyarattanakalin; Chalicheemalapalli Kulala Jayasankar; Wisanu Pecharapa (My University, 2024)
In this work, Er-doped BiVO4/BiFeO3 composites are prepared using the sonochemical process with a difference of rare earth loading compositions. The crystallinity and chemical and morphological structure of as-synthesized samples were investigated via X-ray diffraction, Raman scattering, and electron microscopy, respectively. The diffuse reflectance technique was used to extract the optical property and calculate the optical band gap of the composite sample. The piezo-photocatalytic performance was evaluated according to the decomposition of a Rhodamine B organic compound. The decomposition of the organic compound was achieved under ultrasonic bath irradiation combined with light exposure. The Er-doped BiVO4/BiFeO3 composite heterojunction material exhibited significant enhancement of the piezo-photocatalytic activity under both ultrasonic and light irradiation due to the improvement in charge generation and separation. The result indicates that Er dopant strongly affects the phase transformation, change in morphology, and alternation in optical band gap of the BiVO4 matrix. The incorporation of BiFeO3 in the composite form with BiVO4 doped with 1%Er can improve the photocatalytic performance of BiVO4 via piezo-induced charge separation and charge recombination retardment.
Keywords: Rhodamine B; Advanced Photocatalysis Techniques